Circum-Arctic peat soils resist priming by plant-derived compounds. (May 2023) - Wild, Birgit; Monteux, Sylvain; Wendler, Bernd; Hugelius, Gustaf; Keuper, Frida
Abstract: Rapid Arctic warming increases permafrost thaw and CO2 production from soil organic matter decomposition, but also enhances CO2 uptake by plants. Conversely, plants can also stimulate soil organic matter decomposition near their roots, via rhizosphere priming. The recent PrimeSCale model suggests that this can accelerate Arctic soil carbon loss at a globally relevant rate, and points to large potential contributions from carbon-rich permafrost peatlands. At the same time, the high carbon content of peatlands might render them insusceptible to input of easily available organic compounds by plant roots, which is considered a key component of priming. We here investigated the sensitivity of permafrost peat soils to priming by plant compounds under aerobic conditions that resemble the dominant rooting zone, based on a 30-week laboratory incubation of peat soils from five circum-Arctic locations. No significant change in CO2 production from peat organic matter by organic carbon addition was observed, and an increase of 24% by organic nitrogen addition. Combining our data with a literature meta-analysis of priming studies showed similar, low priming sensitivity in organic layers of mineral soils, and significantly stronger priming in mineral horizons where organic carbon and nitrogen increased decomposition by 32% and 62%, respectively. Low sensitivity of permafrost peat to input of organic compounds was also supported under anaerobic conditions, by incubation of one soil type. In a new PrimeSCale sensitivity analysis, we show that excluding peatlands would reduce estimates of priming-induced carbon loss from the circum-Arctic by up to 40% (up to 18 Pg) until 2100, depending on peat priming sensitivity. While our study suggests a limited effect of plant-released organic compounds on peat decomposition, it does not preclude an effect of vegetation on decomposition under natural conditions, through other mechanisms. The large range of possible priming-induced peat carbon losses, and expected changes in vegetation and drainage, call for a sharpened focus on the combined effect of living plants on soil processes beyond carbon input, including changes in nutrient and water availability, aggregation, and microbial communities. Highlights: Roots can stimulate soil CO2 production by releasing organic compounds ("priming"). Circum-Arctic peat did not show aerobic priming by organic C, but by organic N. Arctic mineral horizons showed stronger priming than peat and organic layers. Peat insensitivity to priming strongly reduces projected Arctic soil carbon losses.